Mr. Miracle [compact disc, unabridged] : a Christmas novel - Macomber, Debbie (Books On Tape, 2014)
Assigned to help young college student Addie Folsom get her life back on track, guardian angel Harry Mills poses as a teacher and oversees her relationship with contrary neighbor, Erich Simmons, with whom Addie is forced to spend Christmas.